Methodology for Self-assessment of the Teacher and Auxiliary Staff Variable in Medical Colleges - Mabel Rocha Vázquez; Dámaso Roque Díaz de Villegas; Georgina Jiménez Estrada; María Isabel Mantecón Ledo; Pavel Vigo Cuza; Milagros León Regal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: the Ministry of Higher Education has given great importance to monitoring the work performed by higher education institutions, as an essential means to achieve continuous quality improvement. The accreditation is the result of implementing an internal and external evaluation system, aimed at publicly acknowledging that an institution or program meets certain quality requirements. Objective: to present a methodology for self-assessment of the teacher and auxiliary staff variable, in the context of the Universities of Medical Sciences. Methods: a qualitative developmental research focused on the teacher and auxiliary staff variable was conducted at the Faculty of Medical Sciences of the University of Medical Sciences in Cienfuegos. Expert judgment was used to validate the methodology. Their level of expertise was assessed by determining the K coefficient. Results: the proposed methodology was divided into two stages: the first stage is organizational, for identifying key subjects and areas, tasks to develop, training design and schedule, and the second is the implementation stage. Conclusion: the proposed methodology provides the way to self-assess the teacher and auxiliary staff variable with a systemic approach. It was improved based on its implementation into practice and it was validated by expert judgment.